Length‐Based Assessment of an Artisanal Albulid Fishery in the South Pacific: a Data‐Limited Approach for Management and Conservation - Filous, Alexander; Lennox, Robert J.; Clua, Eric E. G.; Cooke, Steven J.; Danylchuk, Andy J. (Marine and coastal fisheries, 2019)
Data‐limited fisheries assessment methods have great potential to help inform small island communities on the status of their fisheries resources. In this paper, we provide a length‐based assessment of an artisanal fishery that primarily targets spawning aggregations of Shortjaw Bonefish Albula glossodonta at Anaa Atoll in the Tuamotu Archipelago of French Polynesia. We assessed the length‐frequency distribution of the spawning stock across a 3‐year period (2016–2018). During this time, male and female Shortjaw Bonefish were fully recruited to the fishery at age 4 and age 5, respectively. Fishing mortality was over two times the range of natural mortality for this species (i.e., 0.21–0.32), and based on these estimates of natural mortality, the annual spawning potential ratio of the population was between 7% and 20% across the sampling years. The majority of the catch was sexually mature, with 78, 95, and 95% of the annual female catch in 2016, 2017, and 2018, respectively, being equal to or greater than the length of first maturity (i.e., 48 cm FL). However, every fisheries indicator and biological reference point suggested that the fishery was overexploited and in need of management intervention. To this aim, the community of Anaa (1) established an Educational Managed Marine Area, which overlaps with the Shortjaw Bonefish migratory corridor adjacent to Tukuhora village and (2) instated a temporal rahui (a traditional conservation method) inside the Educational Managed Marine Area during the peak months of the spawning season.